Non-compliance of antihypertensive medication among female patients - Ahamed, Kazi Shamim; Salma, Umma; Begum, Nazma; Murshed, A KM (Journal of Dhaka National Medical College & Hospital, 2018)
Background: Hypertension is an overwhelming global challenge. It is one of the most important modifiable risk factors for cardiovascular diseases. Poor compliance with treatment is the most important cause of uncontrolled blood pressure.A number of concerning antihypertensive drug compliance has been conducted worldwide, although a little research in this topic has been conducted in Bangladesh. So, it will be time demanded job to study the noncompliance to anti hypertension drugs in patients with essential hypertension. In this study, we want to see the socio demographic features associated with treatment noncompliance in hypertension. Methodology: It was a cross sectional type of Observational study conducted at department of medicine, Dhaka National Medical College. Study done from 1st October 2013 to 31st March 2014 on 100 female patients with diagnosed Hypertension. Result: In this study about 64% of the patients were non compliant to treatment and 36% were compliant to their treatment. Location,family size, and monthly income of patients family were socioeconomic factors that had statically significance when it comes to compliance. In my study reasons for not taking the medication included misconception to antihypertensive drug (31.25%) others like forgetfulness, journey (20.31%) and poor financial condition (17.19%). J. Dhaka National Med. Coll. Hos. 2018; 24 (02): 23-26